A 10-Day-Old Murine Model of Coxsackievirus A6 Infection for the Evaluation of Vaccines and Antiviral Drugs - Jiang, Zaixue; Zhang, Yaozhong; Lin, Huayuan; Cheng, Qingqiu; Lu, Xiaomei; Liu, Wenkuan; Zhou, Rong; Zhong, Baimao; Tian, Xingui (Frontiers in Immunology, 2021)
Coxsackievirus A6 (CVA6) is recognized as a major enterovirus type that can cause severe hand, foot, and mouth disease and spread widely among children. Vaccines and antiviral drugs may be developed more effectively based on a stable and easy-to-operate CVA6 mouse infection model. In this study, a wild CVA6-W strain was sub-cultured in newborn mice of different ages (in days), for adaptation. Therefore, a CVA6-A mouse-adapted strain capable of stably infecting the mice was generated, and a fatal model was built. As the result indicated, CVA6-A could infect the 10-day-old mice to generate higher levels of IFN-γ, IL-6, and IL-10. The mice infected with CVA6-A were treated with IFN-α1b at a higher dose, with complete protection. Based on this strain, an animal model with active immunization was built to evaluate antiviral protection by active immunization. The three-day-old mice were pre-immunized with inactivated CVA6 thereby generating IgM and IgG antibodies within 7 days that enabled complete protection of the pre-immunized mice following the CVA6 virus challenge. There were eight mutations in the genome of CVA6-A than in that of CVA6-W, possibly attributed to the virulence of CVA6 in mice. Briefly, the CVA6 infection model of the 10-day-old mice built herein, may serve as an applicable preclinical evaluation model for CVA6 antiviral drugs and vaccine study.